Modifying functional brain networks in focal epilepsy by manual visceral-osteopathic stimulation of the vagus nerve at the abdomen - Lehnertz, Hendrik; Broehl, Timo; Rings, Thorsten; von Wrede, Randi; Lehnertz, Klaus (Frontiers in Network Physiology, 2023)
Non-invasive transcutaneous vagus nerve stimulation elicits therapeutic effects similar to those produced by invasive vagus nerve stimulation and is thus considered as a potential supplementary treatment option for a wide range of diseases, including epilepsy. Here, we present an alternative, non-invasive stimulation of the vagus nerve, which is performed manually viscero-osteopathically on the abdomen (voVNS). We investigate the impact of short-term voVNS on various local and global characteristics of EEG-derived, large-scale evolving functional brain networks from a group of 20 subjects with and without epilepsy. We observe differential voVNS-mediated alterations of these characteristics that result in a reconfiguration of networks and a modification of their stability and robustness properties. Although the impact of such a non-pharmaceutical intervention on clinical decision-making in the treatment of epilepsy needs to be assessed in future studies, our findings may add to the current discussion on the importance of the gut-brain axis in health and disease.